Peran Jenis dan Partisipasi Politik - Thobagus Moh Nu’man; Emi Zulaifah (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2003)
Political participation is the activity of private citizens for the purpose of influencing government decision making. Gender role is defined as behavioral predisposition of a person as relates to his/her gender. Gender role can be grouped into feminine, masculine and androgyny and unclassified. This study is aimed at finding relationship between gender role and political participation among college female activists. The subjects of this study were female students from various university in Yogyakarta, with age ranging from 18-28 years. Gender role was mesured by using gender role scale, modelling one from Bem Sex Role Inventory. Political participation was mesured using polical participation scale which shows the following indicators: voting activity, organizational participation, political discussion, lobbying and finding connection. The data was analyzed by one way ANOVA. The results indicated that there is no differences in political participation as seen from four different gender roles(F = 1,273; P > 0,05). Practical and research implications are discussed.Key words: Gender rope, political participation, women, Bem’s Sex Role Inventor